Effect of sedated colonoscopy with different cost coverage on improving compliance with colorectal cancer screening in China - Zhuo, Lin; Kong, Yunxin; Chen, Siting; Ma, Yue; Cai, Ting; Pan, Jianqiang; Wang, Xiuying; Gao, Yihuan; Lu, Hang; Li, Xinyue; Zhao, Hongying; Mackay, Louisa; et al. (Frontiers in Oncology, 2023)
Background Colorectal cancer is the third most common cancer worldwide. Colonoscopy is the gold standard for colorectal cancer screening. However, the colonoscopy participation rate in China is much lower than that in Europe and the United States. As only non-sedated colonoscopies are offered in colorectal cancer screening programs in China, the absence of sedation may contribute to this gap. Methods To explore the effect of free and partially participant-paid sedated colonoscopy on improving colorectal screening participation, we conducted a cross-sectional study under the framework of the Cancer Screening Program in Urban China in Xuzhou from May 2017 to December 2020. The Quanshan district was set as the control group and provided free non-sedated colonoscopy, the Yunlong district was set as a partial cost coverage group and offered partially participant-paid sedated colonoscopy, and the Gulou district was set as the full cost coverage group and offered free sedation colonoscopies. Multivariate logistic regression was used for multivariate analysis of colonoscopy participation and colorectal lesion detection rates between the groups. Results From May 2017 to May 2020, 81,358 participants were recruited and completed questionnaire, 7,868 subjects who met high-risk conditions for CRC were invited to undergo colonoscopy. The colonoscopy participation rates in the control group, partially cost coverage, and full cost coverage groups were 17.33% (594/3,428), 25.66% (542/2,112), and 34.41% (801/2,328), respectively. Subjects in the partial and full cost coverage groups had 1.66-fold (95% CI: 1.48–1.86) and 2.49-fold (95% CI: 2.23–2.76) increased rates compared with those in the control group. The adjusted PARs for the partially and the full cost coverage group was 9.08 (95% CI: 6.88–11.28) and 18.97 (95% CI: 16.51–21.42), respectively. The detection rates of CAN in the control, partial-cost coverage, and full-cost coverage groups were 3.54% (21/594), 2.95% (16/542), and 5.12% (41/801), respectively. There were no significant differences in the detection rates between the group. However, sedated colonoscopy increases costs. Conclusion Sedated colonoscopy increased colonoscopy participation rates in both the partial and full cost-covered groups. A partial cost coverage strategy may be a good way to increase colorectal cancer participation rates and quickly establish a colorectal cancer screening strategy in underfunded areas.